Tools to evaluate the impact of nutrition delivery on muscle and physical-related outcomes in critical care: a scoping review - Rozali, Nur Shazleen Nisha; Azahari, Nuraniza; Mohamed Nor, Noraishah (IIUM Journal of Orofacial and Health Sciences, 2025)
Understanding the impact of nutrition delivery on critically ill patient-centered outcomes is crucial. Patient-centered outcomes should be physical-related due to the natural course of catabolism experienced during critical illness. This review aims to map the existing tools used in research to evaluate the impact of nutrition delivery on muscle and physical-related outcomes among intensive care unit (ICU) patients. A search was conducted in PubMed and Scopus, initially yielding 502 articles published since 2010 on the topic using search terms related to ICU patients, muscle and physical outcomes, and nutrition delivery. Articles were screened based on inclusion criteria, resulting in 45 articles included in the analysis. Findings indicated that the outcome domains used ranged from muscle strength, muscle mass, to function. Imaging techniques and performance-based measures were the most used type of tools, with varying comprehensiveness, precision, simplicity, and feasibility. Despite most studies using repeated measurements throughout ICU stays, challenges in performing comprehensive assessments were reported. This review provides an overview of the assessment tools utilized in ICU nutritional research, highlighting the variability of choice that can be suited with researcher’s objectives and the availability of resources. To improve consistency and comparability across studies, future research should focus on developing standardized protocols for selecting appropriate tools to measure the effects of nutrition delivery on muscle and physical-related outcomes.